(untitled) (Journal of Misan Researches, 2024)
The topic of the sensory image, in its general sense, represents a starting point from which poets begin to enrich their poetic experiences and paint their artistic paintings that express their intellectual visions, feelings and emotions, taking the living reality mixed with imagination as a basis and a source that helps them to form these various images. It is the poet’s tool and mirror that reflects his poetic methods in Intellectual presentation and artistic formation. This research came to address the sensory images of the pre-Islamic poet Aws bin Hajar, and shows his poetic experiences, which were filled with visions, ideas and feelings, in a beautiful artistic style with profound connotations, using his poetry collection, according to the types of senses in man, and what he perceives from each sense according to The type of stimulus for that image, and an explanation of its use of them through what is seen, heard, smelled, touched, or tasted. As for the research plan, it proceeds according to the descriptive and analytical method based on examining texts, divided into an introduction, a preface, and two topics, one of which is: the concept of the poetic image and the sensory image. In the second section, we talked about Aws bin Hajar and his poetic status, and the patterns of sensory images in the poetry of Aws bin Hajar, ending with a conclusion with the main results that the research reached.